Not just the top five journals: A recipe for European economists - Magnus Henrekson; Lars Jonung; Mats Lundahl (Research Institute of Industrial Economics (IFN), 2025)
We provide a critical analysis of the adoption of the US "top-five model" by European economics academia. This model prioritizes publications in five elite journals, heavily influencing the career trajectories of doctoral students and researchers. It highlights the inefficiencies and social costs of this system, including the overemphasis on narrowly focused research topics and methodologies that align with US editorial preferences. This undermines innovation, interdisciplinary exploration, and economic research on issues of high social relevance in the home countries. The dominance of US institutions in setting these standards, disadvantages European scholars. We propose reforms for more diverse evaluation criteria that account for local relevance and broader scholarly contributions, suggesting that such changes would better align with European academic and societal needs. These adjustments aim to create a more balanced and impactful academic landscape while fostering a wider range of meaningful research outputs.
Keywords: A11; A14; I23; J44; J62; 330; Criteria for hiring and promotion; European economics; Pluralism; Research productivity